Sistema inteligente de suporte a análise da qualidade da energia elétrica em regime permanente - ROCHA, Gabriel Vianna Soares (Universidade Federal do Pará, 2017)
This work presents the development of software that provides a computational environment so that the user can carry out analyzes of Quality of Eletrical Energy (QEE) following the rules stipulated by the National Eletrical Power Agency (ANEEL) through the Distribution Procedures (PRODIST). Also it is possible to do analysis of contribution of impacts caused by the injection of harmonics in the electric network, pointing out the possible percentage shares of contribution of each Consumer Unit (UC), through modules that perform a sensitivity study through Computational Intelligence (CI) techniques as Artificial Neural Network (ANN) Regression Trees (RT) and Simple Linear Regression (LR). For the construction of the models are used time series data of current and voltage harmonics that were obtained through measurement campaigns.